Decomposition and Release Rate of asystasiagangetica (l.) T. Anderson Litter Nutrient using Litterbag Method - Asbur, Yenni; Purwaningrum, Yayuk (International Journal of Engineering and Technology, 2018)
The research aimed to determine the rate of decomposition and release of A. gangetica litter in conditions without shading and shading, and in turn it can be simulated the effects of environmental factors on the decomposition rate and contribution of A. gangeticalitter nutrients to the soil. Research was carried out at Research Farm, Faculty of Agriculture, UISU, Medan, North Sumatra, from January to April 2018. The study used a non-factorial randomized block design with five replications. The treatment is shade which consisting of two levels namely without shading, and with 50% shading. The results showed that the litter weight of A. gangetica decreases with the length of the decomposition period. The decrease in litter weight of A. gangetica is more influenced by the decomposition period than the shade treatment. However, decomposition rate, decreased nutrient concentration in litter tissue, and increased litter release of A. gangetica is affected by shading and decomposition period. Decomposition rate, decrease in litter concentration and release of litter nutrients more quickly in conditions without shadingby the longer decomposition period.Â Â Â